Implementasi Regresi Linear dan Single Exponential Smoothing Dalam Prediksi Harga Saham ANTM - Paidi, Imam; Tundo, Tundo; Rasiban, Rasiban; Suropati, Untung (Department of Computer Engineering, Universitas Wiralodra, 2024)
This study focuses on using linear regression and single exponential smoothing (SES) models to predict the share price of PT Aneka Tambang Tbk (ANTM). Data from Yahoo! Finance covering the period from 2005 to 2023 is used. The linear regression model establishes a relationship between the current and previous stock prices, while the SES model smoothes out fluctuations and captures shortterm trends. The findings reveal that both models are highly accurate in predicting ANTM stock prices. However, the SES model is less consistent in capturing shortterm trends, suggesting its effectiveness lies in capturing seasonal and short-term trends in the ANTM stock price data. This research is significant as it contributes to the development of accurate and reliable stock price prediction models, which can assist investors and players in the capital market in making informed investment decisions. The results also provide a foundation for future research on applying more complex and sophisticated forecasting models for stock price prediction.